Computer-Integrated Manufacturing, Cyber-Physical Systems and Cloud Manufacturing – Concepts and relationships. (October 2015) - Yu, Chunyang; Xu, Xun; Lu, Yuqian
Abstract: Computers are deeply entrenched in modern manufacturing systems, giving rise to technologies such as Computer Integrated Manufacturing, Cyber-Physical Systems and most recently Cloud Manufacturing. These technologies have evolved based on existing or similar technologies or manufacturing paradigms. Some misunderstandings exist among these technologies. In spite of similarities, there are sufficient differences among themselves. To start off, the circumstances under which these technologies were incepted and developed are different. There are different methodologies associated with them. Discussions in this paper are made in relationship to Information Technology, Industry and Services.